2019
DOI: 10.1108/jfra-09-2018-0079
|View full text |Cite
|
Sign up to set email alerts
|

The value relevance of accounting information in the MENA region

Abstract: Purpose The purpose of this paper is to examine the value relevance of accounting information in the Middle East and North Africa region (MENA) region with an emphasis on the potential impact of IFRS adoption. This paper aims to not only examine the value relevance of accounting information in the MENA region but also draw comparisons between Gulf countries (GCC) and non-GCC country firms to determine whether there are distinct differences across the two regions. Design/methodology/approach To investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…The results of this study are consistent with the model results obtained by Ohlson (1995), which accounting and non-accounting data affect the market value of firms. Besides, these findings coincide with the results obtained by Willett (2003), Cooke et al (2009) Bhargava (2014 for, Eriabie & Egbide (2016), El-Diftar & Elkalla (2019 and Camilleria et al (2019). However, the findings of this study in Turkey are not in line with the results of Elbakry et al (2017) for German and U.K.…”
Section: Discussing the Findings With The Literaturesupporting
confidence: 60%
“…The results of this study are consistent with the model results obtained by Ohlson (1995), which accounting and non-accounting data affect the market value of firms. Besides, these findings coincide with the results obtained by Willett (2003), Cooke et al (2009) Bhargava (2014 for, Eriabie & Egbide (2016), El-Diftar & Elkalla (2019 and Camilleria et al (2019). However, the findings of this study in Turkey are not in line with the results of Elbakry et al (2017) for German and U.K.…”
Section: Discussing the Findings With The Literaturesupporting
confidence: 60%
“…Another similar study by Albarrak (2011) reported that the accounting information was value relevant (as indicated by the R 2 results) throughout the study period. A more recent study by El‐Diftar and Elkalla (2019) compares value relevance among the MENA region countries. Their findings suggest IFRS had a negative impact on the value relevance of the studied groups.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…A review of prior relevant literature shows several limitations in conducting the analysis of value relevance research: for example, improper implementation of models (Belassi and Elbarrad, 2020), neglecting the use of a deflator (Alnodel, 2018), using a multi‐country comparison by overlooking the country‐specific context (El‐Diftar and Elkalla, 2019), using a small sample size (Oraby, 2017), ignoring the use of valuation models (Ebaid, 2021) or failing to use the R 2 comparison tests (Oraby, 2017; Alnodel, 2018). Therefore, a more refined research design is necessary to provide more valid results on the impact of IFRS adoption on the value relevance of accounting information of listed firms on the Saudi stock market.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, conducting research into income influential items at the firm level may be useful for many financial statements users, including boards of directors, managers, auditors, financial analysts, policy makers and regulators. The firm-level information is associated with most engaging uses of income and its related items such as compensation, debt, supply and licensing contracts (Givoly and Palmon, 1982; Zeghal, 1984; Dhaliwal et al , 2008; Haw et al , 2015; Kim and Zhang, 2016; Badu and Appiah, 2018; Salehi et al , 2018; Barth et al , 2019; El-Diftar and Elkalla, 2019; Salehi et al , 2019; Salehi et al , 2020). Therefore, a substantial amount of evidence is obtained from extensive firm-level literature.…”
Section: Introductionmentioning
confidence: 99%